PEMUTUSAN PEMINANGAN SECARA SEPIHAK MENURUT PERSPEKTIF HUKUM ISLAM - Heri nawati (Al-Bayyinah, 2018)
This study addresses the issue of termination peminangan unilaterally according to the perspective of Islam, mainly to do with the status of money shopping (dui menre) in the perspective of Islamic law. In addition, it also aimed to find out the Customs termination peminangan sanctions unilaterally according to the perspective of Islamic law. Dui Menre included in the structure of indigenous norms that have been rooted in the culture of Bugis and has become a requirement for the continuation of the Bugis culture within the Covenant of marriage. The issue of Islamic law menre Dui entered in terms of the tahsiniyyah even though according to the custom of Dui menre belongs to the category in terms of wedding customs. So the customs in this regard is under the law the legitimate and a requirement that could cancel the halal in the one is not accepted. Therefore, the law menre Dui according to Islamic law is mubah (permissible) because of its position as a grant.